Hubungan Antara Locus Of Control Internal Dengan Komitmen Organisasi - Insani, Putri Gema; , Achmad Dwityanto, S.Psi, M.Si (2017)
The organization is important for an organization because they can make someone might have spent work hard to achieve organizational goals. An employee locus of control internal is likely to have commitments high evaluation organization, they have tended to be positive attitude and motivation high for commit to keep his organization. But , if they have a negative trend low and motivation to keep commit on his organization. The aim of this research is to know the relationship between internal locus of control with commitment organization, so the authors propose the hypothesis "there is a positive relationship between internal locus of control with commitment organization". Subjects in this study Primary school teachers civil servants ( civil servants ), which totaling 80 subjects. The sampling technique is a non random, all individuals in the population will not be an equal chance of are only sampled. Based on the discussion has concluded that in this research technique is used purposive non random sampling, a subject as sample research based certain features. The measure instrument which used to reveal research variables there are 2 kinds of measure instrument, namely: (1) the scale of internal locus of control, and (2) commitment organization. Data analysis in this study is uses of product-moment correlation. Based on the anlysis results, so that obtained correlation between internal locus of control with commitment organization of (r) amount of 0,840 with p=0,000 where p < 0,01, this means there is a very significant positive relationship between internal locus of control with commitment organization. That is, the higher the internal locus of control then the higher commitment organization, and reverse the lower internal locus of control then also the lower commitment organization. The empirical mean of internal locus of control variable is amount of 94,48 and hypothetic mean is amount of 75. It shows that empirical mean > hypothetic mean that illustrates that teachers civil servants has a high internal locus of control. Further the empirical mean of commitment organization variables is amount of 123,18 and hypothetic mean is amount of 97,5. It shows that empirical mean > hypothetic mean that illustrates that teachers civil servants has a high commitment organization. The role of the internal locus of control toward commitment organization is amount of 70,5% that means there is still 29,5% that affect commitment organization, for example: environmental factors, eksternal locus of control.